2018
DOI: 10.1016/j.corsci.2018.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of corrosion fatigue crack initiation on martensitic stainless steel in high cycle fatigue regime

Abstract: This paper presents an analytical model for assessing the corrosion fatigue crack initiation life on a martensitic stainless steel X12CrNiMoV12-3 in high cycle fatigue regime (between 10 5 and 10 7 cycles). Based on in-situ electrochemical measurements during corrosion fatigue tests in NaCl aqueous solution, the corrosion fatigue crack initiation mechanism was identified. Two main stages were investigated: (i) the fracture of the passive film by slip bands and (ii) the free dissolution of the metal developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 46 publications
0
9
0
2
Order By: Relevance
“…The corrosion fatigue coupling could also be particularly harmful for some materials [13,30,52]. Different coupling mechanisms were pointed out in the literature, such as local persistent slip bands inducing pit initiation [14,23], loading driving pit growth morphology [40,52], corrosion at crack tip [31] or hydrogen embrittlement [11]. These coupling mechanisms could potentially decrease the lifetime more drastically than it could be predicted by considering corrosion and fatigue phenomena independently.…”
Section: Introductionmentioning
confidence: 99%
“…The corrosion fatigue coupling could also be particularly harmful for some materials [13,30,52]. Different coupling mechanisms were pointed out in the literature, such as local persistent slip bands inducing pit initiation [14,23], loading driving pit growth morphology [40,52], corrosion at crack tip [31] or hydrogen embrittlement [11]. These coupling mechanisms could potentially decrease the lifetime more drastically than it could be predicted by considering corrosion and fatigue phenomena independently.…”
Section: Introductionmentioning
confidence: 99%
“…Another powerful electrochemical technique, which allows measurement of corrosion rates and learning about corrosion mechanisms is electrochemical impedance spectroscopy (EIS), in which an alternating potential or current signal is applied to an electrochemical cell and the resulting current (or potential) is measured. The technique has been successfully applied on stainless steel under corrosion‐fatigue degradation …”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical variables such as corrosion current density and corrosion potential have been used to assess the damage evolution in corrosion-fatigue experiments. [21][22][23][24][30][31][32] Although current response gives valuable information about the electrochemical kinetics of the corrosion-fatigue system, its measurement commonly requires the application of a certain level of polarization leading to a condition that does not represent the free corrosion behaviour of the material. Meanwhile, some studies 30,31 have shown that the growth of oxide on the surface of the material and the nucleation of microcracks can change the shape of the corrosion potential response during corrosion-fatigue tests of magnesium alloys.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations